What is sponsorship? - Day, Helen (Henry Stewart Talks, 2009)
Definitions of sponsorship, Statistics regarding the sponsorship marketplace, How sponsorship operates including objectives, structure, benefits and evaluation, Core principles in managing sponsorship, Summary of the sponsorship process